1998
DOI: 10.1074/jbc.273.19.11752
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Glycosyltransferase Enzyme from theEscherichia coli K5 Capsule Gene Cluster and Identification and Characterization of the Glucuronyl Active Site

Abstract: Bacterial capsular polysaccharides play an important role in virulence and survival. The Escherichia coli K5 capsule consists of a repeat structure of -4)GlcA-␤(1,4)-GlcNAc ␣(1-, identical to N-acetylheparosan. A 60-kDa protein, KfiC, has been identified as a bifunctional glycosyltransferase, responsible for the alternating ␣ and ␤ addition of each UDP-sugar to the nonreducing end of the polysaccharide chain. Using hydrophobic cluster analysis, a conserved secondary structure motif characteristic of ␤-glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
0
51
0
1
Order By: Relevance
“…The next best heterologous matches for the pmHS enzyme in the data base are KfiA and KfiC proteins from E. coli K5; these two proteins work together to make the heparosan polymer (7,8). There is a good overall alignment of the enzyme sequences if smaller portions of the pmHS ORF are aligned separately with KfiA and KfiC (Fig.…”
Section: Molecular Cloning Of the Type D P Multocida Heparosanmentioning
confidence: 99%
See 1 more Smart Citation
“…The next best heterologous matches for the pmHS enzyme in the data base are KfiA and KfiC proteins from E. coli K5; these two proteins work together to make the heparosan polymer (7,8). There is a good overall alignment of the enzyme sequences if smaller portions of the pmHS ORF are aligned separately with KfiA and KfiC (Fig.…”
Section: Molecular Cloning Of the Type D P Multocida Heparosanmentioning
confidence: 99%
“…At first, KfiC was stated to be a dual-action glycosyltransferase responsible for the alternating addition of both GlcUA and GlcNAc to the heparosan chain (7). However, a later report by the same group reported that another protein, KfiA, was actually the ␣GlcNAc-transferase required for heparosan polymerization (8).…”
mentioning
confidence: 99%
“…The inactivation of the catalytic domain by substitution of both aspartic acids by asparagines has been described for P. multocida hyaluronan synthase PmHAS (9,10) and for PmHS1 (heparosan synthase 1) (11). Here we describe, based on amino acid sequence homology with PmHS1 and with Escherichia coli heparosan synthase KfiC and KfiA (12)(13)(14), the construction of the two PmHS2 single action transferases (PmHS2-GlcUA ϩ and PmHS2-GlcNAc ϩ ). Both the characterization of the single action transferases and a detailed study of the polymerization process of PmHS2 allowed us to investigate the initiation process of heparosan chains.…”
mentioning
confidence: 99%
“…Both conservative and non-conservative mutations abolished N-acetylglucosaminyltransferase activity. Similarly, mutation of any one of several aspartic acid residues in KfiC resulted in total loss of the relevant GlcUA-transferase activity (10). These data, however, are not definitive because the mutagenized enzymes did not retain any activity, and it is difficult to draw conclusions from any inactive enzyme because of the potential for global misfolding.…”
mentioning
confidence: 71%
“…The K5 antigen region 2 encodes four proteins designated KfiA to KfiD involved in synthesizing the sugar chain (8). KfiA was discovered to act as an ␣4-N-acetylglucosaminyltransferase (9) whereas KfiC is the ␤4-glucuronyltransferase (although initially the latter was erroneously reported to be a dual action enzyme responsible for heparosan polymerization (10)). Therefore, in E. coli the formation of the heparosan polymer occurs by the concerted action of KfiA and KfiC proteins.…”
mentioning
confidence: 99%